1984
DOI: 10.3354/meps018241
|View full text |Cite
|
Sign up to set email alerts
|

Population structure of daytime surface swarms of the euphausiid Meganyctiphanes norvegica in the Bay of Fundy

Abstract: Daytime surface swarms of the euphausiid Meganyctiphanes norvegica occurring off Brier and Long Islands in the Bay of Fundy were studied during the summers of 1979 to 1983. Individual swarms were found to have highly skewed sex ratios; both male dominated and female dominated swarms were encountered but female swarms were more common. Individuals in surface swarms comprised a restricted part of the population when compared to samples taken at depth and when compared to the population structure of this species … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
37
0

Year Published

1986
1986
2010
2010

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(42 citation statements)
references
References 21 publications
5
37
0
Order By: Relevance
“…In spite of the obvious importance of swarming to understanding the biology of krill relatively little has been published on the variation in composition of individual swarms or schools of krill, with the exception of studies on surface swarms of E. superba (e.g. Marr 1962) and on other euphausiids (Endo 1984, Nicol 1984, O'Brien 1988. Such observations have either been made by divers (Hamner et al 1983) or on samples taken from 0 Inter-ResearchPrinted in Germany aimed net hauls (Quetin & Ross 1984, Watkins et al 1986.…”
Section: Introductionmentioning
confidence: 99%
“…In spite of the obvious importance of swarming to understanding the biology of krill relatively little has been published on the variation in composition of individual swarms or schools of krill, with the exception of studies on surface swarms of E. superba (e.g. Marr 1962) and on other euphausiids (Endo 1984, Nicol 1984, O'Brien 1988. Such observations have either been made by divers (Hamner et al 1983) or on samples taken from 0 Inter-ResearchPrinted in Germany aimed net hauls (Quetin & Ross 1984, Watkins et al 1986.…”
Section: Introductionmentioning
confidence: 99%
“…A further problem with the use of M. norvegica as an experimental animal in a laboratory setting is that, like all krill, they are social animals invariably found in swarms (Aitken, 1960;Nicol, 1984). Isolation of krill in aquaria has undoubtedly led to data being produced that are difficult to interpret, for example in the study of swimming energetics (Ritz, 2000) and circadian migratory rhythms (Gaten et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The fact that this phenomenon occurred in both sexes indicates that it might be age rather than sex that influences the level of risk undertaken at this stage of the life cycle. The occurrence of surface swarms in this (Nicol 1984) and other euphausiid species (Euphausia pacifica, Nakamura 1992; E. superba, Marr 1962; Thysanoessa inermis, Hanamura et al 1989;T. raschii, Timofeyev 1994) is another example of where older individuals spend increasing amounts of time in the upper layers.…”
Section: Influence Of Life-cycle Strategiesmentioning
confidence: 99%
“…Meganyctiphanes norvegica is one of the most prolific migrators, capable of ascending over 700 m in an hour (Tarling et al 1999a). Nicol (1984) and Tarling et al (1999b) showed that the migration behaviour of this species is modified by spawning and moulting activity, but such behaviour accounts for less than 5% of its lifecycle and, in the case of moulting, affects both sexes in similar ways (Tarling et al 1999b). Sexual differences in DVM outside of the brief periods of spawning and moulting has been little considered, yet the consequences in terms of relative mortality rates is likely to have a large influence on the population dynamics of this species.…”
Section: Introductionmentioning
confidence: 99%